THE RELATIONSHIP OF TEACHERS' TEACHING SKILLS TO LEARNING OUTCOMES OF THE SUBJECT HISTORY OF ISLAMIC CULTURE AT SMA NEGERI 4 DOMPU - Khatimah, Husnul; Justita, Inul; Julianti, Sakina; Syahrl, Syahril (Pimpinan Cabang Muhammadiyah Kramat Jati, 2023)
Teaching skills are quite complex professional competencies, as an integration of various teacher competencies in a complete and comprehensive manner. The aim of this research is to determine the relationship between teachers' teaching skills and learning outcomes in the History of Islamic Culture subject at SMA Negeri 4 Dompu. The members of this research population were all class X students. The sampling technique used a proportional statified random sampling technique with a sample size of 52 students. The research results show that there is a relationship between teachers' teaching skills and learning outcomes. After testing using the person product moment correlation formula, a correlation value of 0.288 was obtained, it can be concluded that there is a relationship between teacher teaching skills and learning outcomes.